2022
DOI: 10.3390/hydrology9080132
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Climate Change on Water Resources and Crop Production in Western Nepal: Implications and Adaptation Strategies

Abstract: Irrigation-led farming system intensification and efficient use of ground and surface water resources are currently being championed as a crucial ingredient for achieving food security and reducing poverty in Nepal. The potential scope and sustainability of irrigation interventions under current and future climates however remains poorly understood. Potential adaptation options in Western Nepal were analyzed using bias-corrected Regional Climate Model (RCM) data and the Soil and Water Assessment Tool (SWAT) mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 51 publications
(65 reference statements)
0
1
0
Order By: Relevance
“…Climate change and increasing water scarcity affect the food supply (about 70 percent on average) for agriculture (FAO, 2017). Regional Climate Model outputs also suggested that the average annual maximum temperature could decrease by 1.4 °C, and the average annual minimum temperature may increase by 0.3 °C from 2021 to 2050 (Risal, 2022).…”
Section: Temperaturementioning
confidence: 99%
See 1 more Smart Citation
“…Climate change and increasing water scarcity affect the food supply (about 70 percent on average) for agriculture (FAO, 2017). Regional Climate Model outputs also suggested that the average annual maximum temperature could decrease by 1.4 °C, and the average annual minimum temperature may increase by 0.3 °C from 2021 to 2050 (Risal, 2022).…”
Section: Temperaturementioning
confidence: 99%
“…The unmanaged water resources do not contribute to the irrigation system However, an imbalance in nature results in the consequences of agricultural production, and obviously human health. Only about 4.7% of available water in Nepal has been effectively utilized (Risal, 2022). Nepal's domestic product has been affected by Global warming /climate change increased flooding, and heat stress on crops/ livestock are expected to be a continual drag on growth (WB.…”
Section: Introductionmentioning
confidence: 99%
“…This is because a traditional water source such as rainfall cannot supply water adequately throughout the year. In addition, climate change has resulted in lower yields as growing seasons become shorter and temperatures rise; hence, irrigation appears to be a viable option if adequately harnessed (Risal et al, 2022). Such concerns also motivate this study given that the unsustainable use of water may lead to damaging long‐term and limiting prospects for future generations (Uhlenbrook et al, 2022).…”
Section: Introductionmentioning
confidence: 99%